2000
DOI: 10.1016/s0218-625x(00)00061-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Scale Observations of Surface Alloying, Surface Phase Transitions, Domain Coarsening, and 3D Island Growth Pb on Cu(100)

Abstract: Low energy electron microscopy (LEEM) is used to investigate the dynamics of Pb overlayer growth on CU(1OO).By following changes in surface morphology during Pb deposition, the amount of Cu transported to the surface as the Pb first alloys into the surface during formation of the c(4x4) phase and subsequently de-alloys during conversion to the c(2x2) phase is measured.We find that the added coverage of Cu during alloying is consistent with the proposed model for the c(4x4) alloy phase, but the added coverage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A continuation of our computational studies on Ni growth for (110) and (111) surfaces in addition to the (100) surface, found that the presence of H on Ni(100) catalyzes the mobility of lone Ni adatoms across the surface resulting in accelerated island formation on time scales of the deposition itself. As part of the continuing interest in understanding step-dynamics and 3-d island growth, we also examined how H atoms modified the Erlich−Schwoebel step edge barriers that govern 3-d island formation . In our own earlier work, , the H-atom mobility was handled by redistribution based upon Boltzmann statistics due to the wide separation in time scale separating the H and Ni adatom mobilities, and for surface atom mobilities our test calculations confirmed that Boltzmann redistributions were reasonable.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…A continuation of our computational studies on Ni growth for (110) and (111) surfaces in addition to the (100) surface, found that the presence of H on Ni(100) catalyzes the mobility of lone Ni adatoms across the surface resulting in accelerated island formation on time scales of the deposition itself. As part of the continuing interest in understanding step-dynamics and 3-d island growth, we also examined how H atoms modified the Erlich−Schwoebel step edge barriers that govern 3-d island formation . In our own earlier work, , the H-atom mobility was handled by redistribution based upon Boltzmann statistics due to the wide separation in time scale separating the H and Ni adatom mobilities, and for surface atom mobilities our test calculations confirmed that Boltzmann redistributions were reasonable.…”
Section: Introductionmentioning
confidence: 77%
“…The experimental interest in growing thin, smooth metallic films has led to a theoretical effort in understanding microscopic growth and mobility mechanisms involved in metallic films. Of additional importance in the growth process is the role impurities play in the growth mechanism, and some experimental reports have noted that impurities can help to induce the layer-by-layer growth of a metal film in some cases, or can hinder the layer-by-layer growth in other cases. In particular, a hydrogen impurity absorbed on metal surfaces has been noted as affecting metal growth by either hindering metal adatom self-diffusion, or by enhancing it, depending on the system . In some of the work that we have been involved in, experimental results were reported that H induces layer-by-layer growth of Cu(100), and similar computational predictions were noted for the closely related fcc metal Ni(100) surface …”
Section: Introductionmentioning
confidence: 99%
“…Many recent computational studies of adatom diffusion and crystal growth based upon single atom and correlated atom hopping across activation energy barriers have recently been reported, a partial sampling of which we note in the references. Our approach uses the theoretical and computational details that we have described more extensively in refs −3, so only a brief summary is given here. We break the computational problem into two parts: the calculation of activation energy barriers to find rate constants, and the Kinetic Monte Carlo (KMC) simulation of the growth process based upon those rate constants.…”
Section: Theoretical and Computational Backgroundmentioning
confidence: 99%
“…The experimental interest in growing thin, smooth metallic films has led to a theoretical effort in understanding microscopic growth and mobility mechanisms involved in metallic films. The growth of metallic films can be described in terms of the competition of the rates for various processes involved: the deposition rate, the mobility rate of a lone adatom across a surface, the condensation of a lone adatom with other adatoms to form islands, the evaporation of such islands as lone adatoms break off, and the peripheral diffusion of atoms along the edge of an island.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation